2020
DOI: 10.3389/fevo.2020.556856
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid Pesticides Are More Toxic to Honey Bees at Lower Temperatures: Implications for Overwintering Bees

Abstract: The honey bee (Apis mellifera) is an important pollinator as well as an important test model for pesticide effects on other insect pollinators. Honey bees have been experiencing high mortality in both the United States and worldwide. Pesticide exposure has been identified as one of the many stressors causing this mortality. Effects of various pesticides have been measured for multiple responses such as learning, memory performance, feeding activity, and thermoregulation. These studies were conducted at many di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 60 publications
0
11
0
1
Order By: Relevance
“…Although the ERA process in its current state does not explicitly incorporate the interactive effects of climate and pesticides, there is growing recognition that temperature can affect the risks of pesticides to pollinators. For instance, honey bees were more sensitive to imidacloprid and thiamethoxam at 24°C than 35°C (Saleem et al 2020). This reduction in toxicity at 35°C was not due to degradation of the pesticide itself; nonlinearities may arise when heat stress is high enough to induce physiological responses that allow bees to better tolerate neonicotinoids (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although the ERA process in its current state does not explicitly incorporate the interactive effects of climate and pesticides, there is growing recognition that temperature can affect the risks of pesticides to pollinators. For instance, honey bees were more sensitive to imidacloprid and thiamethoxam at 24°C than 35°C (Saleem et al 2020). This reduction in toxicity at 35°C was not due to degradation of the pesticide itself; nonlinearities may arise when heat stress is high enough to induce physiological responses that allow bees to better tolerate neonicotinoids (2020).…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial ecosystems, winter bees may be exposed to neonicotinoid insecticides through insecticides‐coated seeds sown in the winter time (Botías et al, 2015; Woodcock et al, 2017) and through feeding on insecticide‐contaminated wax and pollen that bees collected from previous seasons (Sanchez‐Bayo & Goka, 2014). Laboratory experiments have shown that some neonicotinoid insecticides, such as thiamethoxam and imidacloprid, are more toxic to honey bees at low winter temperatures than at higher summer temperatures (Saleem et al, 2020). Moreover, large field studies found that neonicotinoid insecticides reduced overwintering success (Woodcock et al, 2017).…”
Section: Interactions Between Multiple Stressors and Wintermentioning
confidence: 99%
“…Experimental studies aimed at understanding the ecological and physiological mechanisms of effects may be necessary to improve opportunities for generalization and prediction [52]. For example, both high [56] and low [57] temperatures can increase pesticide toxicity in insects through different physiological mechanisms, suggesting that a clearer understanding of these mechanisms [58] may be necessary to predict the interactive effects of thermal stress and pesticide exposure.…”
Section: The Complexity Of Global Change Effectsmentioning
confidence: 99%